Confronting Colonial Narratives: How Destination Museum Exhibits Can Sustainably Engage with Social Justices Issues - Scott R. Sanders; Michael R. Cope; Taryn J. Frerichs (Tourism and Hospitality, 2025)
As museums serve as major tourist destinations, ensuring the sustainable presentation of exhibits addressing social justice issues, such as colonial legacies, is increasingly critical. This study examines how one destination museum engaged with its colonial past through a temporary exhibit designed to challenge traditional narratives and amplify marginalized perspectives. The primary objective is to assess whether such temporary interventions foster lasting engagement with colonial histories or risk becoming fleeting gestures that ultimately reinforce hegemonic narratives. Using Gramsci’s theory of hegemony and the concept of moral licensing as analytical frameworks, this research systematically analyzes the content of both original and supplementary exhibit labels to evaluate their impact on visitor engagement with colonial histories. Specifically, this study addresses two key research questions: (RQ1) What new historical narratives and perspectives on colonialism did visitors encounter through the inclusion of supplementary museum labels addressing colonial legacies? (RQ2) What insights can be drawn from the addition and subsequent removal of these labels to inform future strategies for fostering sustained critical engagement with social justice issues, particularly colonial histories, in museum settings? Findings indicate that the addition of supplementary labels provided tourists with a deeper, more critical understanding of the museum’s colonial history and helped disrupt hegemonic narratives. However, as the exhibit was temporary, the removal of these labels revealed the risks of moral licensing, where short-term efforts may justify a return to dominant perspectives. This research contributes to the literature by demonstrating that to effectively and sustainably engage visitors with social justice issues, destination museums must integrate marginalized narratives into permanent or recurring exhibits. While even modest interventions, such as additional museum labels, can challenge established narratives, sustained efforts are essential to ensure that tourists continue engaging with critical social justice issues.